Expression and Toxicity of Bacillus thuringiensis subesp. israelensis strains harbouring the gene encoding the main mosquitocidal 8-endotoxin from Bacillus thuringiensis subesp. medellin - REALPE, MAURICIO; ORDUZ, SERGIO (Revista Colombiana de Entomología, 1998)
The 94 kDa protein (MED94) of: B. thuringiensis subsp. niedellin has been recognized as the main toxicity factor of this bacterium to mosquito larvae. From a genomic library evaluated by immunoblot with polyclonal antibodies raised against MED94, it was possible to identify, done, and sequence the gene encoding this endotoxin. This report describes the subcloning procedure of this gene using the phagemid pBlueScript SK(-) as a donor of a 3.3 kph fragment flanked EcoRIHindfll (RH3). Two shuttle vectors (pBU4 y pMK3), harboring replication origins compatible with B. thuringiensis, were the receptors of the gene. These plastics differ in source, copy number, selection marker, and structural-segregational stability. The transforming procedure of B. thuringiensis subsp. israelensis through electroporation with each construct gave rise to recombinant strains of B. thuringiensis subsp. israelensis 4Q2-81 (acrystalliferous strain) and B. thuringiensis subsp. israelensis 1884 (H14 serotype, used in commercial formulations). this strain expressed the introduced gene, according to Western blot and toxicity hioassays results. Recombinants were tested by means of Southern blot experiments to detected the presence and integrity of the introduced gene, it was also analyzed the expression of native ti—endotoxins uf B. thuringiensis subsp. israelensis 1884. The half lethal concentration (LC50) of crystal protein was estimated bay Probit analysis, as a measure of the toxicity against third instar larvae of Aedes aegvpti exponed tu samples of the purified parasporal crystal s. and compared to the toxicity produced by native strains.